2005
DOI: 10.1007/s00213-005-0174-5
|View full text |Cite
|
Sign up to set email alerts
|

MDMA (Ecstasy) and human dopamine, norepinephrine, and serotonin transporters: implications for MDMA-induced neurotoxicity and treatment

Abstract: Rationale: 3,4-Methylenedioxymethamphetamine (MDMA, designated as "Ecstasy" if illicitly marketed in tablet form) induces significant decrements in neuronal serotonin (5-HT) markers in humans, nonhuman primates, and rats as a function of dosing and dosing regimen. In rats, MDMA-mediated effects are attributed, in part, to selective high-affinity transport of MDMA The affinity of MDMA for the human SERT in transfected cells does not clarify the apparent selective toxicity of MDMA for serotonin neurons, although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
125
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 82 publications
(104 reference statements)
12
125
0
1
Order By: Relevance
“…These differences may be attributable to their differing mechanisms of action. MDMA-related effects in the brain are widespread; it potently releases the monoamine neurotransmitters dopamine, serotonin, and norepinephrine in part by inducing carrier-mediated release through their respective transporters (Han and Gu, 2006;Verrico et al, 2007;Rothman et al, 2001), which likely contributes to its wide range of physiological, subjective, and behavioral effects. In rodents, endogenous and exogenous oxytocin binds in brain regions associated with mood, arousal, and reward (Gimpl and Fahrenholz, 2001) and also increases levels of dopamine, serotonin, and norepinephrine (Shahrokh et al, 2010;Vincent and Etgen, 1993;Yoshida et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may be attributable to their differing mechanisms of action. MDMA-related effects in the brain are widespread; it potently releases the monoamine neurotransmitters dopamine, serotonin, and norepinephrine in part by inducing carrier-mediated release through their respective transporters (Han and Gu, 2006;Verrico et al, 2007;Rothman et al, 2001), which likely contributes to its wide range of physiological, subjective, and behavioral effects. In rodents, endogenous and exogenous oxytocin binds in brain regions associated with mood, arousal, and reward (Gimpl and Fahrenholz, 2001) and also increases levels of dopamine, serotonin, and norepinephrine (Shahrokh et al, 2010;Vincent and Etgen, 1993;Yoshida et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its effects on dopamine, serotonin, and norepinephrine in the brain (Han and Gu, 2006;Rothman et al, 2001;Verrico et al, 2007), MDMA also appears to release oxytocin. In rats, MDMA increases oxytocin levels in the brain, and oxytocin receptor antagonists attenuate the behavioral effects of MDMA (Thompson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, SERT has a lower affinity than the norepinephrine transporter, but a higher affinity than the dopamine transporter for MDMA, as shown for the rat (Rothman et al, 2001) and for the human protein (Pifl et al, 2005;Verrico et al, 2007). In addition, MDMA might indirectly affect dopamine levels via 5-HT release (Koch et al, 1997).…”
Section: Pharmacodynamic Effects Of Mdma On Dopamine and 5-ht Levels mentioning
confidence: 99%
“…MDMA is a known substrate and an inhibitor of the 5-HT transporter (SERT), noradrenaline transporter (NET) and dopamine transporter (DAT; Verrico et al, 2005). Once inside the cell, MDMA causes the release of endogenous neurotransmitter back into the extracellular space, again via the monoamine transporters, resulting in a substantial rise in the level of extracellular neurotransmitter (Green et al, 2003;Pifl et al, 2005).…”
mentioning
confidence: 99%
“…In light of the central role of monoamine transporters in mediating the pharmacological actions of MDMA, it was decided to investigate the effects of the MDMA analogues on NET and SERT transport in vitro, using two separate mammalian cell lines. Although the significance of DAT in mediating both the physiological and potentially toxicological effects of MDMA should not be underestimated (Colado et al, 2004;Breier et al, 2006;Rothman and Baumann, 2006), MDMA has typically demonstrated a greater inhibitory potency at NET and SERT compared to DAT in vitro (Rothman and Baumann, 2003;Pifl et al, 2005;Verrico et al, 2005). Consequently, it was decided to perform this investigation using NET and SERT.…”
mentioning
confidence: 99%